Chrysanthos S. Chrysanthou, Plutarch’s Parallel Lives . Narrative Technique and Moral Judgement, De Gruyter (“Trends in Classics - Supplementary Volumes” 57), Berlin-Boston 2018, pp. 228, ISBN 978-31-105-7298-8 - Curnis, Michele (ΠΗΓΗ/FONS, 2020)
Book review